Journal Information Page – TOC - Arora, Ashish; Gittelman, Michelle; Kaplan, Sarah; Lynch, John; Mitchell, Will; Siggelkow, Nicolaj (Strategic Management Journal, 2015)
The Strategic Management Journal seeks to publish the highest quality research with questions, evidence and conclusions that are relevant to strategic management and engaging to strategic management scholars. We receive manuscripts with a diverse mix of topics, framings, and methods, and our acceptances reflect this diversity.